Religious Moderation: Humanitarian Values from Pope Francis Arrival in Indonesia at The End of 2024 - Putra, Ahmad; Adnan, Syaiful; Fitria, Yulia; Efendi, Syafrizal; Andrianto, Andrianto; Prasetya, Bima (Yayasan Abdurrauf Cendekia Nusantara, 2025)
a history where Indonesia was visited by one of the world figures named Pope Francis who is the highest leader of the world's Catholic church. He came with the aim of voicing a message of unity between religious communities towards a better humanity and living in harmony in differences. Althousgh in addition, he wanted to meet with the Catholic community in Indonesia and build cooperation between his country, namely the Vatican and Indonesia. The common thread in this study is to see what forms of religious moderation emerged with the arrival of Pope Francis to Indonesia, where the majority of Indonesian society is filled with Muslims. This study uses a qualitative approach with the library research method, in which case the researcher utilizes information obtained from scientific works, books, and reliable sources. The results of this study show that: first, the arrival of Pope Francis was greeted with joy by the majority of Indonesian people, second, Pope Francis' mission is to voice people to live in harmony within the framework of religious differences, third, Pope Francis kissed the hand of the Grand Imam of the Istiqlal Mosque and the Grand Imam of the Istiqlal Mosque kissed Pope Francis' head, fourth, security guards through the Police and TNI during Pope Francis' activities in Indonesia